Simultaneous water uptake from shallow groundwater and drip irrigation: Lysimeter experiments with ceramic cups - Ben Cohen; Ido Nitsan; Ilan Ben‐Noah; Shmulik P. Friedman (Vadose Zone Journal)
Abstract This study investigates the interplay between shallow groundwater and on‐surface drip irrigation in facilitating water uptake of agricultural crops. Lysimeter experiments utilizing ceramic cups mimicking plant roots provide insights into wetting patterns within the root zone and water balance components. Results reveal that while plants can effectively utilize shallow groundwater even with limited root systems, higher irrigation rates diminish groundwater contribution to water uptake. Conversely, shallow groundwater enhances water uptake from on‐surface irrigation, reducing drainage at low irrigation rates. The findings underscore the potential of groundwater as a supplementary water source for crops, offering practical implications for optimizing supplemental irrigation strategies and sustainable water management in agriculture. When the vertical distance between active roots and the water table exceeds a characteristic length of the soil, it disrupts the continuity of the liquid water phase. As a result, intensive capillary upward water flow, against gravity, cannot be reliably described by Darcy's law. It becomes imperative to formulate a practical continuum theory to more accurately depict capillary rise in such scenarios.